41PCustomisation of therapeutic strategy in metastatic colorectal cancer by use of liquid biopsies: Updated results of an observational study. (7th November 2019) - Kastrisiou, M; Zarkavelis, G; Kougioumtzi, A; Tzallas, C; Saloustros, E; Kotsakis, A; Papadopoulou, E; Nasioulas, G; Batistatou, A; Magklara, A; Pentheroudakis, G
Abstract: Background: Metastatic colorectal cancer (mCRC) affects 20% of patients diagnosed with colorectal malignancy and is a major cause of cancer-related death worldwide. Epidermal growth factor receptor (EGFR) blockade with monoclonal antibodies, in combination with chemotherapy, has been shown to benefit patients with RAS wild type tumours. Our project explores real-time assessment of mCRC mutational profile, by use of two methods of circulating tumour DNA (ctDNA) analysis, and its potential to better guide therapeutic decisions. Methods: Baseline plasma samples were prospectively collected from 64 patients at diagnosis of mCRC and at disease progression. Analysis of KRAS and NRAS exons 2, 3 and 4 was performed with the highly sensitive BEAMing digital polymerase chain reaction (PCR) and next-generation sequencing (NGS). In a subgroup of patients, with baseline RAS mutations, mid-treatment liquid biopsies were performed, to assess the change in ctDNA RAS mutational load as response biomarker. Mutational status of matched tumour tissue, generated with a conventional PCR-based method or NGS, was prospectively recorded for all patients. Results: Preliminary results of our study, presented at the EACR-ESMO Joint Conference on Liquid Biopsies, have shown detection of RAS mutations in the ctDNA from over 50% of patients, with a satisfactory plasma-tissue concordance. An update on these data, as well as on the predictive value of ctDNA RAS mutational load dynamics, will be presented. Disease progression data, in light of baseline RAS status, will also be revisited, as almost 20% of patients have progressed on first-line treatment. In addition, the concordance of BEAMing and NGS as liquid biopsy methods is to be studied in a subgroup of patients with available plasma samples. Conclusions: The larger sample size and the maturity of this updated analysis further add on the value of our work, the results of which remain in line with the literature. Our study serves as a real-life example of the potential of liquid biopsies to detect RAS mutation status changes, allowing for precision-oncology therapeutic approaches in the continuum of care of metastatic colorectal cancer patients. Legal entity responsible for the study: Department of Medical Oncology, University General Hospital of Ioannina. Funding: Amgen, Hellenic Society of Medical Oncology (HeSMO) and Society for Study of Clonal Heterogeneity of Neoplasia (EMEKEN). Disclosure: G. Pentheroudakis: Research grant / Funding (institution): Amgen. All other authors have declared no conflicts of interest.